Social Consolidation in the Arab Ampel Community of Surabaya: Continuity of the Iwadh Tradition from a Sociological Perspective - Asta, Naufal Robbiqis Dwi; Maulana, Achmad Rifky Ibnu; Syarif, Ahsan Ahmad; Sari, Amelia Ayu Fatmah (Journal of Islamic Thought and Philosophy, 2024)
This article aims to describe the framework and role of the Iwadh tradition in the Arab Ampel neighborhood of Surabaya. The Iwadh tradition is a socio-religious practice where members of the Arab community visit one another and seek mutual forgiveness during Eid al-Fitr as a way of completing their Ramadan worship. This tradition is particularly noteworthy for its ability to foster social bonds that transcend differences, including interfaith boundaries. The research utilizes methods such as interviews, observations, and documentation, analyzed through a sociological approach inspired by Emile Durkheim's perspective. The study finds that the Iwadh tradition plays a significant role in building social and spiritual connections. By exchanging visits and sharing food, it strengthens collective identity and social solidarity, maintaining elements of mechanical solidarity in the face of modernization.